Manajemen Pendidikan Islam Dalam Membentuk Karakter Siswa Di Sekolah Islam - Hasibuan, Rahmadani (Jurnal Pendidikan Agama Islam, 2024)
Education plays an important and central role in developing human potential, including intellectual potential. Through education, it is hoped that transformation can develop positive character and change that character from evil to good. National education mandates schools/madrasahs as formal educational institutions to carry out learning processes that enable social and cultural development that creates national character and civilization. The aim of this research is to describe the management of Islamic education in developing the character of Madrasah Ibtidaiyah students. This research method uses a qualitative method with a descriptive analytical research type. The results of this research indicate that Islamic education management is necessary for the development of student character. Therefore, it is necessary to plan character education, organize character education, implement character education, and monitor character education. Character education is documented and integrated into the curriculum. The development of character education is not only passed on to school members such as teachers and students, but also to parents and the local community. Character values ​​are then integrated into the learning plan.